A novel catalyst system for the synthesis of N, N′-Methylenebisacrylamide from acrylamide. Issue 1 (1st January 2017) - Avşar, Abdullah; Gökbulut, Yener; Ay, Burak; Serin, Selahattin
Abstract: N, N′-Methylenebisacrylamide (MBAA), which is an important raw material in a widely industrial area, was synthesized using convenient catalysts. The synthesized monomer was fully characterized by the elemental analysis, fourier transform infrared (FT-IR) spectroscopy, thermogravimetric analysis (TGA), 1 H-NMR, 13 C-NMR, GC/MS, and high performance liquid chromatography (HPLC) analysis. Six different homogeneous and heterogeneous catalysts were used to obtain maximum monomer yield. The MBAA was obtained with 95% yield by using Cu(II) catalyst containing carboxylate groups ligands.